Age at menarche in urban school-going girls: association between socio-economic status, BMI and physical activity - Behel, Amrita; Raje, Leena (International Journal Of Community Medicine And Public Health, 2021)
Background: Menarche, one of the most reliable markers of pubertal maturity, is a result of a complex interplay between genetic and environmental factors. Since accelerated pubertal development is an important determinant of prognostic disease risk, especially in developing countries, attention must be focused on this important public health aspect. Methods: Total 200 school-going girls aged between 10-15 years studying in municipal, public-funded and private schools in Mumbai were included in the study based on the inclusion criteria of having attained menarche only in the last three months. Sociodemographic and anthropometric details were collected using a structured schedule and physical activity data was collected using the physical activity questionnaire for older children and adolescents. Results: Socioeconomic status and family size were found to significantly influence the age of onset of menarche (p<0.001). Anthropometric indices of height, weight and BMI were found to have significant negative correlations indicating that taller, heavier girls reached menarche earlier than their shorter and lighter peers (p<0.000). Level of physical activity was also found to be an important contributing factor to age at menarche such that a higher level of physical activity was observed in girls with higher mean menarcheal age (p<0.000). Conclusions: Age at menarche was found to be influenced by factors such as socioeconomic status, BMI and physical activity.